The impact of the quality of transport networks on economic competitiveness in the European Union - Cezar Teclean (CES Working Papers, 2022)
This paper assesses the impact of transport infrastructure quality on economic competitiveness in the European Union (EU), context in which we argue that the quality of the different modal transport networks has a differentiated contribution on competitiveness. The purpose of our analysis aims to quantify the qualitative contribution of each modal transport network to economic competitiveness in the EU. The econometric quantification of the mentioned impact emphasizes a contributory hierarchy as follows: the quality of port and railroad infrastructure contributes most substantially to economic competitiveness, followed by the quality of the air transport infrastructure, the inland waterways and the road network. Based on the iterated results, we sequenced the EU member states with the lowest quality of networks with the highest impact on competitiveness. Thus, we identified the states for which the priority improvement of the quality of the port and railway infrastructures would significantly improve their economic competitiveness.
Keywords: 330; transport infrastructure; sustainable quality; economic competitiveness; spatial competitiveness; European Union